2019
DOI: 10.1111/obr.12877
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of system dynamics and agent‐based obesity models: Evaluating obesity as part of the global syndemic

Abstract: Summary The problem of obesity has recently been reframed as part of the global syndemic—the co‐occurring, interacting pandemics of obesity, undernutrition, and climate change that are driven by common underlying societal drivers. System science modeling approaches may help clarify how these shared drivers operate and the best ways to address them. The objective of this paper was to determine to what extent existing agent‐based and system dynamics computational models of obesity provide insights into the share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 82 publications
(194 reference statements)
1
35
0
1
Order By: Relevance
“…The majority of published studies using system approaches to address child health have focused on healthy eating and obesity, with a paucity of studies using systems approaches to other child health outcomes [19,21,[26][27][28][29]. The current study seeks to extend the scope of a systems mapping approach beyond single child health outcomes to address inequalities in child health more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of published studies using system approaches to address child health have focused on healthy eating and obesity, with a paucity of studies using systems approaches to other child health outcomes [19,21,[26][27][28][29]. The current study seeks to extend the scope of a systems mapping approach beyond single child health outcomes to address inequalities in child health more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…As referenced earlier, to our knowledge, there are three reviews of migration ABMs relevant to the aim of this review, including Klabunde and Willeken's review focusing on decision-model choice including integration of social networks (n = 22 included publications) [2], Thober and colleagues' review of ABMs of environmental-migration linkages (n = 21) [4], and Bell and colleagues' brief background review on ABMs exploring migration push-pull factors to present their migration ABM framework (nonsystematic, n = ~ 8) [3]. Other examples of ABM reviews include previous reviews on the use of ABM to study other social or health science topics, such as urban crime (n = 45) [32], non-communicable diseases (NCDs) (n = 22) [33], obesity (n = 38) [34], public health (non-systematic, n = ~ 45) [21], and health systems (n = 11) [35]. These reviews reported notable increased interest in and application of ABM methods in their respective field of study, despite still small yields compared to other reviews including different methods.…”
Section: Examples Of Other Abm Reviewsmentioning
confidence: 99%
“…Therefore, the data extraction process captured the authors' affiliations and study aim, model inputs, model development, model process and the analysis and validation methods completed by the authors. This method is similar to systematic reviews of ABMs on other social or health science research topics that focused on the study design, model specifications (agents, environment, decision rules), and model analysis (sensitivity analysis, model validation) for data extraction and synthesis [33,34,[38][39][40][41]. The data extraction tool was informed by the guiding questions outlined in the Overview, Design Concepts and Details + Decision-Making (ODD + D) protocol for ABM development, which is an adaptation of the original Overview, Design Concepts and Details (ODD) protocol developed to standardize descriptions of individual-based models (IBMs) and ABMs [5,42,43].…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that systematic reviews are increasingly being conducted and published for Systems Science‐related and simulation methodologies (Carey et al, 2015; Luke & Stamatakis, 2012). A number of systematic reviews addressing non‐communicable diseases which included system dynamic (SD) studies have been conducted, but these have been mostly combined with other System Science's approaches such as Agent‐Based Modelling (ABM) and Discrete‐Event Simulation (Levy et al, 2011; Morshed, Kasman, Heuberger, Hammond, & Hovmand, 2019; Nianogo & Arah, 2015; Skinner & Foster, 2013; Xue, Slivka, Igusa, Huang, & Wang, 2018). Although there are some systematic reviews including SD studies in the literature, the application of systematic reviews to inform the SD modelling process is very scarce and barely appreciated (Darabi & Hosseinichimeh, 2020).…”
Section: Introductionmentioning
confidence: 99%